Filarete Der Architekt der Renaissance als Demiurg und Pädagoge - Hub, Berthold (2020)
»Filarete: The Architect of the Renaissance as Demiurge and Educator« is the first monograph investigating the Libro architettonico, written by Filarete (Antonio di Pietro Averlino) between 1460 and 1464. The book is presented in the form of a dialogue between the author and the Duke of Milan, Francesco Sforza, along with his son Galeazzo Maria Sforza, concerning the planning, founding and construction of the city of 'Sforzinda', named after its patron, as well as a city connected with it located on the sea coast.